PERAN KEPUASAN MEMEDIASI PENGARUH CITRA LPD TERHADAP LOYALITAS NASABAH LPD DESA ADAT ABIANTUWUNG DI TABANAN: Indonesia - Gusti Alit Suputra (Fakultas Ekonomi Universitas Warmadewa, 2020)
This study aims to examine the role of satisfaction mediating the effect of LPD images on the loyalty of LPD customers in Abiantuwung Adat Village in Tabanan. This research was conducted using the Propotionate Stratified Random method in which the method of taking samples from population members randomly and proportionally. The sample in this study were 70 people. Data were collected using a questionnaire and used Technical Analysis Path. The results of the study show that 1) LPD image has a significant positive effect on employee performance, this means that a positive image perceived by the customer can affect customer loyalty in conducting transactions in the Abiantuwung Indigenous Village LPD, because what the customer wants is in accordance with the reality, 2) Citra LPD influences significant positive effect on customer satisfaction, because the image of the LPD has a large role in building customer trust, with a positive image given, the customer who feels loyal to become a customer in the LPD Abiantuwung Adat Village, 3) customer satisfaction has a significant positive effect on customer loyalty, this means satisfied customers will create a sense of loyalty to Abintuwung LPD. 4) customer satisfaction can mediate the relationship between LPD image and customer loyalty The results of this study are expected to be a reference for Indonesian financial institutions, especially in the LPD of Abiantuwung Adat Village in identifying variables that can affect customer loyalty, especially satisfaction that can enhance the LPD image, in order to improve customer quality.